Place-based displacement: touristification and neighborhood change - Cocola-Gant, Agustín (2023)
Relying on extensive fieldwork, in this paper I give voice to long-term residents in the city center of Barcelona, Spain, and explore how they feel about the tourism-led transformation of the place in which they live. I found that the alteration of the place causes the breaking down of emotional and material attachments that people have with the area and, in turn, the process leads to feelings of expulsion and mental distress. Therefore, I discuss the concept of place-based displacement within the context of touristification, and suggest that housing market disruptions caused by tourism and short-term rentals are insufficient in understanding why communities resist and oppose the penetration of tourism in their places. Drawing on the conceptualization of displacement as suggested by gentrification scholars and from contributions regarding the psychology of place, the paper argues that, regardless of whether spatial dislocation takes place, touristification disintegrates the places people belong to and rely on for their daily lives, which therefore leads communities to experience disruptions to their mental health as well as feelings of dispossession, anger, and frustration.